Experimental Psychology and the Generosity of the Spirit - Callaway, Kutter (International journal for the study of the Christian church, 2020)
The first part of this article argues that David Brown and Gavin Hopps' most recent book, The Extravagance of Music, makes a significant contribution to the theological scholarship on music. At the same time, it suggests that, by allowing Jeremy Begbie to serve as their primary interlocutor, Begbie's work tends to over-determine the terms, conditions, and scope of their text. By way of response, the second part focuses on the field of inquiry known as empirical aesthetics', and considers whether empirical testing might provide the basis for mediating between the different positions outlined by Brown and Hopps, and serve as a means for moving beyond the present impasse within the conversation on the theological significance of music.